The Representation of Environmental Economic Practices in Historical Texts and Archives - Gustriansyah, Edy; Junaidi, Eko Wahyu; Zulianto, Mukhamad (Universitas Tanjungpura, 2026)
This study examines the representation of environmental economic practices in local historical texts and archives in Indonesia by situating the relationship between economic activity and the environment within a critical historical perspective. Environmental economics has often been approached through technocratic and contemporary policy frameworks, leaving the historical dimensions that shape patterns of resource exploitation and management relatively underexplored. Using a qualitative descriptive approach based on textual and archival analysis, this research investigates a range of local historical sources, administrative archives, and policy documents from the pre–New Order period, the New Order era, the Reformasi period, and the contemporary context. The findings reveal a significant shift in the representation of environmental economic practices, from adaptive systems grounded in local ecological knowledge toward an extractive development paradigm legitimized by the state, followed by the reproduction of similar logics under decentralization and the discourse of the green economy. Historical texts not only document environmental economic practices but also function as discursive instruments that shape societal and governmental perceptions of nature. This study argues that environmental economic issues cannot be separated from their historical construction and the power relations that sustain them. Therefore, a historical approach is essential to fostering critical reflection in the formulation of environmental economic policies that are more equitable, context-sensitive, and sustainable.